Penyuluhan Hukum Tentang Perlindungan Konsumen Terhadap Transaksi Berbasis Online Berdasarkan Ketentuan Hukum Nasional di Desa Aikmual - Zunnuraeni Zunnuraeni; Zainal Asikin; RR. Cahyowati; Rizky Yuniansari (Unram Journal of Community Service, 2021)
The increasing number of online-based transactions, particularly e-commerce, has raised a variety of legal issues that can harm consumers. To regulate online-based transactions, a number of laws and regulations were established. Online transactions have also now reached the villages. As for the village of Aikmual, where devotional activities will be carried out, online transactions, especially online buying and selling, have been commonly carried out by mothers. About one-third of women in Aikmual village have become accustomed to buying and selling online through various e-commerce platforms. To avoid losses to consumers, the Extension Team of the Faculty of Law, Mataram University, will conduct legal counseling activities regarding Consumer Protection in online-based transactions in Aikmual village. This legal counseling method is carried out through lectures, namely the delivery of material by the extension team and by means of discussion with the target audience. The conclusion of this extension activity is that there are several problems related to online transactions faced by the target audience, including discrepancies between goods ordered and those received by consumers, concerns about the security and legality of online investment, and lack of public understanding about the legal mechanisms that can be taken by consumers when facing problems in online transactions